A PubMed Citations Search Study on the Prevalence of Epiphora in the General Adult Population - Haefliger, Ivan O.; Haefliger, Yasmina D.; Pimentel de Figueiredo, Ana Rosa (Klinische Monatsblätter für Augenheilkunde, 2020)
Purpose To assess the prevalence of epiphora in the general adult population based on PubMed search citations.Methods 1) Electronic PubMed MEDLINE database search (September 13, 2019) with the terms (Medical Subject Headings or MeSH) “prevalence” and “epiphora”, 2) “epiphora” and “dry eye”, and 3) “prevalence”, “epiphora”, and “dry eye”. Review of all citations from these searches containing the term “epiphora” either in their abstract or title.Results 1) PubMed search retrieved 2 617 137 citations for “prevalence”, 26 135 for “epiphora”, and 2554 for “prevalence” AND “epiphora”. Within the latter 2554 citations, the word “epiphora” appeared in the abstract or title of only 109 citations (< 5%). None of these 109 citations assessed the prevalence of epiphora in the adult general population as the primary end point. Only one abstract mentioned that out of 125 patients, 7.2% indicated, retrospectively, that they had already had epiphora before cataract surgery. Two large population-based studies addressed the incidence of epiphora, not in adults, but in infants (20%) and children (7.7%). 2) The PubMed search showed 22 487 citations for “dry eye”, 30 211 for “epiphora” OR “dry eye”, and up to 18 414 joint citations for the terms “epiphora” AND “dry eye”. These 18 414 citations were 70 and 82% of the number of MeSH citations for “epiphora” and “dry eye” alone, respectively. Of these 18 414 citations, the word “epiphora” only appeared in 131 citations (< 1%), one of them being an extra report mentioning a 32% incidence of epiphora among postmenopausal women. 3) The search found 2206 citations for “prevalence” AND “epiphora” AND “dry eye”, with only 10 of them (< 1%) containing the word “epiphora”.Conclusions Despite a large number of citations retrieved by PubMed searches, there seems to be a lack of studies on the prevalence of epiphora in the adult general population. There is apparently also a large number of overlapping PubMed citations retrieved for searches with the terms “epiphora” AND “dry eye”, although more than 99% of them did not even display the word “epiphora”. Although epiphora is considered a common complain, its prevalence in the adult general population deserves to be further assessed.
Keywords: tearing eye; watery eye; blepharitis; keratoconjunctivitis sicca; epidemiology; incidence